Cholesteatoma in a cat. Issue 1 (May 2019) - Alexander, Akash; Mahoney, Paul; Scurrell, Emma; Baines, Stephen
Case summary: A 14-year-old neutered female Burmese cat was referred for investigation of a caudal oropharyngeal mass. CT showed a thin walled cyst-like structure filling and expanding from the right tympanic bulla. Histopathology showed fragments of mildly dysplastic squamous epithelium and aggregates of keratin. These findings were considered consistent with a diagnosis of cholesteatoma. Relevance and novel information: To the best of our knowledge, this is the first reported case of a cholesteatoma in a cat. Cholesteatoma should be considered a differential diagnosis for cats presenting with a caudal oropharyngeal mass, a history of chronic ear disease or a history of previous, surgically managed middle ear disease. Advanced imaging and biopsies should be considered important in the diagnosis of these lesions.